2006
DOI: 10.1111/j.1527-3466.2006.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambrisentan, a Non‐peptide Endothelin Receptor Antagonist

Abstract: Increasing numbers of experimental investigations and recently also of clinical trials strongly suggest an integral involvement of the endothelin (ET)-system in the pathophysiology of a variety of disease states, mainly of the cardiovascular system. Ambrisentan (LU 208075), a selective ET A -receptor antagonist, is an orally active diphenyl propionic acid derivative. It has been shown to have a very promising efficacy to safety ratio in the initial clinical trials. Phase II and Phase III trials with ambrisenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 94 publications
1
31
0
Order By: Relevance
“…Likewise, in a rat model of type 1 diabetes, we observed increased renal inflammation despite animals maintaining normal blood pressure throughout the study . ET A -selective and combined ET A /ET B receptor antagonists have been approved for use in pulmonary hypertension (Rubin et al, 2002;Blalock et al, 2010), but there is a wide variety of cardiovascular-related diseases in which preclinical studies have suggested efficacy (Krum and Liew, 2003;Vatter and Seifert, 2006;Prasad et al, 2009). In recent years, considerable attention has been paid to the possibility of using this class of drugs for the treatment of resistant hypertension and diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in a rat model of type 1 diabetes, we observed increased renal inflammation despite animals maintaining normal blood pressure throughout the study . ET A -selective and combined ET A /ET B receptor antagonists have been approved for use in pulmonary hypertension (Rubin et al, 2002;Blalock et al, 2010), but there is a wide variety of cardiovascular-related diseases in which preclinical studies have suggested efficacy (Krum and Liew, 2003;Vatter and Seifert, 2006;Prasad et al, 2009). In recent years, considerable attention has been paid to the possibility of using this class of drugs for the treatment of resistant hypertension and diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Ambrisentan is an ETA selective antagonist approved in the United States and Europe for the treatment of pulmonary arterial hypertension. 81 Two other candidates for testing would be the ETA and ETB dual antagonists macitentan and bosentan, which are both also approved for the treatment of pulmonary artery hypertension. Macitentan represents an intermediate pharmacological profile between bosentan and ambrisentan, with a 50-fold selectivity for the ETA subtype compared with the ETB subtype.…”
Section: Endothelial and Microcirculatory Dysfunctionmentioning
confidence: 99%
“…10,15,16 The Ambrisentan and Tadalafil in Patients with Pulmonary Arterial Hypertension (AMBITION) trial investigated the efficacy and safety of initial combination therapy with oral, once-daily ambrisentan and tadalafil, as compared with monotherapy with either of these agents, in participants with previously untreated pulmonary arterial hypertension. We chose this combination because ambrisentan, 17 a selective endothelin-Areceptor antagonist, and tadalafil, 18 a phosphodiesterase type 5 inhibitor, target different intracellular pathways and do not have pharmacokinetic interactions. 19 …”
mentioning
confidence: 99%